PENERAPAN METODE MATERIAL REQUIREMENT PLANNING UNTUK MEMINIMUMKAN BIAYA PERSEDIAAN BAHAN BAKU PADA PT. FAJAR PLASINDO - Achmad Sumbaryadi (Paradigma, 2010)
One of the most imfortant things in production activity is how to manage a raw material requirement level in economic level to support production planning activities. An esthablished company usually uses Material Requirement Planning (MRP) method to provide an effective management system of material requirement to minimize inventory cost.This research found out that, manufacture needs to use Material Requirement Planning (MRP) method to minimize the inventory cost. When  manufacture decided to use Material Requirement Planning (MRP) method, they need to support their system in to computerize system and held on the job training for the production staff to use this method. Keywords : Lot Sizing, Inventory Cost, Material Requirement Planning